Effect of HiFoliar nutrient spray on yield and quality of Zizyphus mauritiana Lamk. cv. Seo under agroforestry system - Kumar, Sudhir; Prasad, Rajendra; Kumar, Anil; Dev, Inder; Rizvi, R.H. (Indian Journal of Agroforestry, 2020)
The present study was carried out in three and half years old experimental field of Zizyphus mauritiana (ber) at ICAR-Central Agroforestry Research Institute, Jhansi during 2013-14 and 2014-15, to assess the response of amino acid based commercial formulate i.e. HiFoliar nutrient on yield and yield attributes of ber cv. Seo in Bundelkhand region of central India. The HiFoliar nutrient was sprayed three times at interval of 15 days starting after first fortnight of October, 2013 to all the plants whereas in October, 2014, no spray was done, to evaluate the effect of spray, paired t-test was applied on two years dataset. The observations on fruit yield and yield attributes were recorded in 2014 and 2015. The findings revealed that almost all fruit characters influenced by the application of HiFoliar nutrient, except total soluble sugar and fruit number. The study concludes that three sprays of HiFoliar nutrient at interval of 15 days, at marble stage of fruits, improves fruit quality and yield of ber cv. Seo in semi-arid Bundelkhand region of Central India.